Improvement High Order Think Skill with Think Pair and Share Learning in Social Arithmetic of the Sekolah Menengah Pertama (SMP) School of Medan - Siagian, Pargaulan (Advances in Social Sciences Research Journal, 2019)
The objective of this study is to yield a certain device of learning with think pair and share of outcomes : book of teacher, book of student, learning program plan (LPP), activity sheet of student, authentic assessment in social arithmetic with ability high order thinking in valid, practical, and effective. Procedure to develop them is according to a 4-D model scheme covering the processes of define, design, develop, and disseminate, in a TPS learning model, and RPP in social arithmetic learning. In execution, the process such as prepare component of mathematics learning material of SMP level, to produce books of teacher, book of student, RPP, activity sheet of student (LKS) and assessment to be applied on SMP level refers to material of learning in social arithmetic and existed in ability of high order thinking skill for 2018. To do disseminate is to apply learning material of mathematic to SMP in order to produce: books of teacher, book of student, RPP, LKS, and assessment of high order thinking skill and disseminate them to teachers of SMP and train them accordingly.